Clinical Profile of Pulmonary Tuberculosis Among Inpatients at Bombana District General Hospital, January–September 2025 - Aisyah Amini; Intan Anugrah Pratiwi; Faskal Othneil Pratama Kaperek (Journal of Health Science and Pharmacy, 2026)
Background: Pulmonary tuberculosis (TB) remains a significant global public health problem, with Indonesia ranking second after India in the number of TB cases worldwide. Objective: This study aims to describe the clinical profile of pulmonary tuberculosis patients hospitalized at Bombana District General Hospital during the period of January–September 2025. Methods: This research employed a descriptive method using secondary data from medical records. The variables analyzed included gender, age, main clinical complaints, results of the Molecular Rapid Test (MRT), and chest X-ray findings. A total of 107 patients met the inclusion criteria. Results: The study showed that the majority were male (70.1%) and aged over 60 years (43.0%). The MRT results showed that 28 patients (26.2%) were drug-sensitive positive, 1 patient (0.9%) drug-resistant positive, and 78 patients (72.9%) negative. Chest X-ray results indicated active pulmonary TB in 55 patients (51.4%), pneumonia in 12 patients (11.2%), pleural effusion in 8 patients (7.5%), and pulmonary TB with other diseases in 32 patients (27.1%). The most common clinical symptoms were Dyspnea and productive cough lasting more than 3 weeks (76.6%). Conclusion: The results of the study show that pulmonary tuberculosis is more commonly experienced by elderly male patients with major complaints of the respiratory system. These findings confirm the importance of MRT examinations as well as chest X-rays in helping to establish a more accurate diagnosis.  Keywords: Pulmonary Tuberculosis, Medical Record, Chest X-Ray, Dyspnea, General Hospital